Comparison of Fuel Consumption on a Hybrid Marine Power Plant With Low-Power Versus High-Power Engines - Wu, Zhenying; Thorat, Laxminarayan; Skjetne, Roger (Volume 1: Offshore Technology, 2018)
In this paper, we are comparing fuel consumption on a case study hybrid marine power plant with diesel gensets and batteries. Optimization methods are used to find an optimal operating point for the gensets, under different power demands, with regards to fuel consumption andNOx emissions. Three different power system example configurations for an offshore construction vessel are explored in this study, and the simulations are carried out to compare the resulting fuel consumption and NOx emissions for these power system configurations. publishedVersion Copyright © 2018 by ASME